Karakteristik Biobriket dari Kotoran Sapi dengan Kulit Durian - Arlini Radityaningrum; Bagus Harnawan (Jurnal Teknologi Lingkungan, 2022)
Cow manure derived biobriquette was an alternative fuel from organic materials. Cow manure contained high calorific value which was potential to be a biobriquette material. Durian bark waste was potential as a mixture material. Variation of material composition affected the biobriquette characteristics. This study aimed to investigate the biobriquette characteristics from the main material of cow manure with the mixture material of durian bark. Total mass of biobriquette materials and adhesive was 43 g, which consisted of cow manure and durian bark (90%) and adhesive material (10%). The material composition was varied in accordance to the percentage of the total mass. Tested parameters were moisture content, ash content, volatile matter, fixed carbon, calorific value, flame duration, and compressive strength value. Biobriquette quality standards were based on the Minister of Energy and Mineral Resources Regulation Number 047 of 2006 and SNI Number 1/6235/2000. Parameters of moisture content, ash content, and calorific value were the parameters that determined the highest quality of biobriquettes. The results showed that the highest quality of biobriquettes met the standards in the Minister of Energy and Mineral Resources Regulation Number 047 of 2006 and SNI Number 1/6235/2000. Biobriquettes with a composition of 20% cow manure, 70% durian skin, and 10% adhesive resulted in the highest quality with 0.90% of water content, 0.38% of ash content, 0.52% of volatile matter, 98.40% of fixed carbon, 4,912.11 Cal/g of the calorific value, and 79 minutes of flaming duration.